Clarithromycin attenuates IL-13–induced periostin production in human lung fibroblasts. Issue 1 (December 2017) - Komiya, Kosaku; Ohta, Shoichiro; Arima, Kazuhiko; Ogawa, Masahiro; Suzuki, Shoichi; Mitamura, Yasutaka; Nunomura, Satoshi; Nanri, Yasuhiro; Yoshihara, Tomohito; Kawaguchi, Atsushi; Kadota, Jun-ichi; Rubin, Bruce; et al.
Abstract Background Periostin is a biomarker indicating the presence of type 2 inflammation and submucosal fibrosis; serum periostin levels have been associated with asthma severity. Macrolides have immunomodulatory effects and are considered a potential therapy for patients with severe asthma. Therefore, we investigated whether macrolides can also modulate pulmonary periostin production. Methods Using quantitative PCR and ELISA, we measured periostin production in human lung fibroblasts stimulated by interleukin-13 (IL-13) in the presence of two 14-member–ring macrolides—clarithromycin or erythromycin—or a 16-member–ring macrolide, josamycin. Phosphorylation of signal transducers and activators of transcription 6 (STAT6), downstream of IL-13 signaling, was evaluated by Western blotting. Changes in global gene expression profile induced by IL-13 and/or clarithromycin were assessed by DNA microarray analysis. Results Clarithromycin and erythromycin, but not josamycin, inhibited IL-13–stimulated periostin production. The inhibitory effects of clarithromycin were stronger than those of erythromycin. Clarithromycin significantly attenuated STAT6 phosphorylation induced by IL-13. Global gene expression analyses demonstrated that IL-13 increased mRNA expression of 454 genes more than 4-fold, while decreasing its expression in 390 of these genes (85.9%), mainly "extracellular, " "plasma membrane, " or "defense response" genes. On the other hand, clarithromycin suppressed 9.8% of the genes in the absence of IL-13. Clarithromycin primarily attenuated the gene expression of extracellular matrix protein, including periostin, especially after IL-13. Conclusions Clarithromycin suppressed IL-13–induced periostin production in human lung fibroblasts, in part by inhibiting STAT6 phosphorylation. This suggests a novel mechanism of the immunomodulatory effect of clarithromycin in asthmatic airway inflammation and fibrosis.